Barney's favorite Mother Goose rhymes - White, Stephen, 1952-; Eubanks, Mary Grace (Texas : Barney Publishing, 1993)
Includes original and contemporary nursery rhymes.
G
b
b
Keywords: Mother Goose -- Adaptations; Nursery rhymes; Children's poetry; Nursery rhymes; American poetry